Built to Scale: the project book - Lim Qiao Tong (Nanyang Technological University, 2023)
This final year report presents the findings and outcomes of a collaborative filmmaking project titled "Built to Scale" undertaken by a team of seven creatives. The logline of the film is as follows, "When Lou, the timid, company misfit, builds a miniature model of her office space, she discovers that it has magical abilities that give her control over her architecture firm." The film explores the complexities of workplace culture and its effects on an individual's sense of self. Through this report, the individuals in the team present their working process from the initial concept to the final product, bringing the script to life.